Coherent Separation Detection for Orbital Angular Momentum Multiplexing in Free-Space Optical Communications - Xiaoke Zhang; Yanliang He; Yao Cai; Mingyang Su; Xinxing Zhou; Yu Chen; Shuqing Chen; Yuanjiang Xiang; Lin Chen; Chenliang Su; Ying Li; Dianyuan Fan (IEEE Photonics Journal)
Beams carrying orbital angular momentum (OAM) are very helpful in enhancing the information carrying capacity in free-space optical communications. However, atmospheric turbulence and energy attenuation will seriously affect communication quality and signal transmissions. Here, a novel coherent separation detection technology for OAM mode division multiplexing is proposed, and numerical simulation work is conducted. With the proposed structure, two light beams with different OAM states, each encoded with 16-quadrature-amplitude modulation orthogonal frequency-modulated (QAM-OFDM) signals, can be demultiplexed and allow two orders of magnitude bit error rate (BER) lower than direct separation detection. Moreover, we show the scalability of multiplexing four OAM beams, achieving a 20 m free-space transmission with BER below 3.8 × 10–3 for all channels at signal-noise ratio (SNR) 18 dB. Our results show that coherent separation detection has excellent antinoise performance and can effectively extend the communication distance. It also paves the way for entirely new coherent optical OAM communications.